[BP.05.06] DOES NIGHTTIME HYPERTENSION IMPACT LEFT VENTRICULAR MECHANICS?. (September 2017) - Tadic, M.; Cuspidi, C.; Vukomanovic, V.; Ivanovic, B.; Pencic, B.; Celic, V.
Abstract : Objective: The aim of this study was to evaluate left ventricular (LV) mechanics in individuals with daytime, nighttime and day-nighttime hypertension (HT). Design and method: This cross-sectional study included 236 untreated subjects who underwent 24-hour ambulatory blood pressure (BP) monitoring and complete two-dimensional echocardiographic examination (2DE) including strain analysis. According to current guidelines, night-time hypertension was defined as nocturnal systolic BP > = 120 mm Hg or diastolic BP > = 70 mm Hg and day-time hypertension as systolic BP > 135 mm Hg and diastolic BP >85 mm Hg. Results: Using aforementioned criteria, the study sample included 68 normotensive subjects (29%), 51 isolated daytime HT (22%), 45 isolated nighttime HT (19%) and 72 day-nighttime HT (30%). 2DE LV longitudinal strain gradually and significantly decreased from normotensive subjects across daytime and nighttime HT patients to day-nighttime HT individuals (−21.8 ± 2.6 vs. −19.4 ± 2.3 vs. −18.8 ± 2.4 vs. −17.8 ± 2.1%, p < 0.001, respectively). The same direction of changes was also obtained for 2DE LV circumferential strain (−22.6 ± 3.1 vs. −20.9 ± 2.7 vs. −19.7 ± 2.6 vs. −18.2 ± 2.7%, p < 0.001, respectively). 2DE radial strain was significantly lower in nighttime HT and day-nighttime HT patients than in controls (39.4 ± 8.8 vs. 37.7 ± 9.1 vs. 35.1 ± 7.8 vs. 34.0 ± 8.0, p = 0.001, respectively). LV twist increased from normotensive subjects across daytime and nighttime HT patients to day-nighttime HT individuals (18.0 ± 6.3 vs. 19.7 ± 6.6 vs. 21.4 ± 7.1 vs. 22.2 ± 7.5 < degree>, p = 0.005, respectively). 24 h systolic BP fall was associated with peak LV longitudinal (β=−0.477, p < 0.001), LV circumferential strain (β=−0.405, p < 0.001), and LV twist (β=0.389, p < 0.001) in the whole study population independent of LV mass index and E/e' ratio. Conclusions: Nighttime HT significantly impacts LV mechanics, which gradually deteriorated from normotensive controls, across isolated day- and nighttime HT, to day-nighttime HT. 24-hour systolic BP is associated with LV longitudinal and circumferential strains, as well as LV twist, independently of LV structure and diastolic function.